Innovative teaching and the education management practice of improving the happiness of engineering college students - Kang, Le; Viriyavejakul, Chantana; Tuntinakhongul, Ampapan (My University, 2024)
This study aims to explore the educational management practices associated with innovative teaching, focusing on their impact on the happiness of engineering college students. Through a comprehensive literature review and empirical research, the study analyzes the characteristics of innovative teaching, the learning tendencies of engineering students, the definition and measurement of student happiness, as well as the relationship between innovative teaching and students’ happiness. To collect data, a combination of quantitative questionnaire surveys and qualitative semi-structured interviews was employed. Data were gathered from 300 engineering college students through questionnaires and from 10 representative students through interviews. Through both statistical analysis and content analysis, this study unveils the implementation and effectiveness of innovative teaching among engineering students, as well as the happiness levels of these students, and the connection between innovative teaching and happiness. The research findings demonstrate that innovative teaching is widely adopted among engineering students and significantly enhances their academic performance and learning motivation. Engineering students generally exhibit a high degree of learning autonomy and creativity, actively engaging in practical projects. Furthermore, the happiness of engineering students is primarily reflected in dimensions such as satisfaction with academic achievements, motivation for learning, and support from their social networks. Further analysis reveals a positive correlation between innovative teaching and the happiness of engineering college students. Quantitative analysis establishes a significant positive correlation between innovative teaching and happiness, highlighting the positive impact of innovative teaching on the well-being of engineering students. Qualitative interview data delves into students’ experiences and cognitive changes brought about by innovative teaching, further affirming the beneficial effects of innovative teaching on their happiness.
Keywords: engineering college students; increased sense of happiness; innovative teaching